2013
DOI: 10.1111/vox.12034
|View full text |Cite
|
Sign up to set email alerts
|

Piloting the use of 2D barcode and patient safety‐software in an Australian tertiary hospital setting

Abstract: This pilot study demonstrates that 2D barcode technology and patient safety-software significantly improves the bedside check of patient and blood product identification in an Australian setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 9 publications
0
12
0
1
Order By: Relevance
“…The British Committee for Standards in Haematology (BCSH) Guidelines stated that"the use of a bedside blood tracking system does not replace the role of the well trained and competency assessed clinician who administers blood components" 25) . More advanced systems, such as two-dimensional bar code 26) and radiofrequency identification (RFID) 27) will be introduced in the near future. The economic aspects and availability of products remain issues regarding implementing these technologies.…”
Section: Resultsmentioning
confidence: 99%
“…The British Committee for Standards in Haematology (BCSH) Guidelines stated that"the use of a bedside blood tracking system does not replace the role of the well trained and competency assessed clinician who administers blood components" 25) . More advanced systems, such as two-dimensional bar code 26) and radiofrequency identification (RFID) 27) will be introduced in the near future. The economic aspects and availability of products remain issues regarding implementing these technologies.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were shown in a pilot study in Australia, where data from auditing revealed poor compliance with patient identification pretransfusion. Following the introduction of 2-dimensional bar code technology and patient safety software, audit results revealed correct patient identification improved from 57% to 94% [17].…”
Section: Auditingmentioning
confidence: 98%
“…Machine‐readable identification technology is ideally suited for matching alpha‐numeric identifiers and is very helpful in preventing slip and lapse errors . Systems based on barcoding technology have been used successfully in preventing bedside errors in transfusion as they can address the various human errors that may occur during the transfusion processes . The system would usually consist of patient wristband with barcoded patient identifying information, a mobile printer connected wirelessly to a hand‐held computer with barcode reading function with or without connectivity to the hospital information system.…”
Section: How Can Information Technology Help In Minimizing Bedside Ermentioning
confidence: 99%
“…This helps to reduce the likelihood of operator being distracted and ensure that the correct protocol is being followed. In fact, studies have showed great improvement on the compliance of operators to protocols after implementation of electronic system for blood transfusion. Such system would reduce the number of manual procedures in the transfusion process and thereby reduce human errors.…”
Section: How Can Information Technology Help In Minimizing Bedside Ermentioning
confidence: 99%